Advanced Computational Fluid Dynamics in Bloodstain Pattern Analysis: Investigating Non-Newtonian Properties for Forensic Applications - Vasconcellos, Luiz Gustavo Sousa (2024)
Aiming to fill a significant gap in scientific understanding, we conducted simulations of human and animal blood droplets in free fall and their impact on solid surfaces, exploring the non-Newtonian properties of blood. The results revealed that simple constitutive models, such as the power-law model, are inadequate for forensic contexts due to nonphysical viscosity levels at high or very low shear rates. Comparisons between models showed substantial variations in internal viscosity distribution and the final shape of the droplets, highlighting the importance of accurate models for forensic analysis. This work, although not pioneering, is one of the few in the world to use Computational Fluid Dynamics (CFD) in Bloodstain Pattern Analysis (BPA), indicating a promising path towards constructing a robust framework for interpreting blood evidence. The simulations performed with the MFSim code position this research at the forefront of forensic fluid mechanics, offering new tools to the international community of bloodstain pattern analysts and establishing a promising path for future scientific investigations.